Digital Dissent: How Indonesian and Filipino Journalists Converge with Virtual Communities to Face State Repression - Hasfi, Nurul (Archīum Ateneo, 2024)
Online protest movements have facilitated researchers to access real-time data of microblogging, user metadata associated with accounts, message content, and enabled insights into complex links between social media use and protest movements. Employing emerging computational techniques and conventional qualitative approaches, this study examines the effectiveness of online protest movements in Indonesia and the Philippines. Simultaneously deployed, these protests were organized by journalist groups against repressive state actions that muzzled the press in these countries. The study compares the strategies of the two movements to illustrate the success factors in social media usage that bolstered the participation of the national and global publics, and marshalled international support.